PERILAKU KEBIASAAN KONSUMSI MAKANAN SEBAGAI FAKTOR RISIKO PENYAKIT TIDAK MENULAR PADA REMAJA - Sri Lestari; Yuliaji Siswanto; Dwi Rahayu; Ulya Zulfa (Universitas Ngudi Waluyo, 2021)
Non-Communicable Diseases (PTM) is a disease that is transmitted and is not transmitted to other people with any form of contact. One of the health problems of national and global concern. PTM is currently at risk for all people, including children, adolescents, adults and the elderly. The purpose of this study is to describe the behavior of food consumption habits as a risk factor for non-communicable diseases in adolescents. The population in this study were Semarang District High School students in the 2019/2020 Academic Year, while the sample in this study amounted to 372 students consisting of SMA N 01 Bringin 151 and SMA N 01 Bergas 221 students. The research design used is descriptive, using the Cross-Sectional method that is research in which the measurement of variables is carried out only once at the same time.The results of this study indicate that for risk factors based on gender are 246 people (66.1%) and men as many as 126 people (33.9%). Fruit consumption behavior is less as many as 247 people (66.4%) and enough fruit consumption behavior is 125 people (33.6%). The consumption behavior of vegetables that are lacking is 239 people (64.2%) and vegetable consumption is sufficient as many as 133 people (35.88%). The consumption behavior of sweet foods is often as many as 237 people (63.7%) and the behavior of consumption of sweet foods that are rarely as many as 135 people (36.3%). The consumption behavior of salty foods is often as many as 181 people (48.7%) and the behavior of consumption of salty foods are rarely as many as 191 people (51.3%). Fatty food consumption behavior which is often 207 people (55.6%) and rare fat food consumption behavior 165 people (44.4%).